Servi??os ecossist??micos em avalia????o ambiental estrat??gica e estudos de impacto ambiental analisados em um caso do planejamento rodovi??rio paulista - Turco, Lu??s Eug??nio Gouv??a (2015)
The Ecosystem Services (ES) are the benefits provided by nature and essential for the maintenance of human life and fundamental to promoting sustainable development. The Environmental Impact Assessment, planning tool for decision making in project level, most used in the world, is guided by the Environmental Impact Assessment (EIA). The Strategic Environmental Assessment (SEA) is an instrument that is directed to support the decision of the planning in the decision-making levels prior to the engineering design, but it is not mandatory in the country. This research is to analyze how the SE theme is integrated in environmental studies, in different spheres of planning, run by the traditional practice of Impact Assessment. To this end, it was selected as an object of study, the Mario Covas Ring Road Program that is being implemented in the Metropolitan Region of S??o Paulo. Thus, we propose an analysis of the SE approach in environmental studies of this program and subsequent design levels. Data collection refers to the acquisition of technical documents related to the SEA reports the Beltway Program and EIAs South Section, East and North. For data analysis was adopted a methodological framework previously tested to assess how the SE are present in these technical documents of the Paulista road planning. It was also conducted an analysis of "tiering" of planning, to see if there was an approach to the SE direction in the program SEA and subsequent EIAs. Research shows a limited integration between SE potential in SEA and EIA, revealing limited evidence hierarchy in S??o Paulo road planning.